The Three-item ALERT-B Questionnaire Provides a Validated Screening Tool to Detect Chronic Gastrointestinal Symptoms after Pelvic Radiotherapy in Cancer Survivors. Issue 10 (October 2016) - Taylor, S.; Byrne, A.; Adams, R.; Turner, J.; Hanna, L.; Staffurth, J.; Farnell, D.; Sivell, S.; Nelson, A.; Green, J.
Abstract: Aims: Although pelvic radiotherapy is an effective treatment for various malignancies, around half of patients develop significant gastrointestinal problems. These symptoms often remain undetected, despite the existence of effective treatments. This study developed and refined a simple screening tool to detect common gastrointestinal symptoms in outpatient clinics. These symptoms have a significant effect on quality of life. This tool will increase detection rates and so enable access to specialist gastroenterologists, which will in turn lead to improved symptom control and quality of life after treatment. Materials and methods: A literature review and expert consensus meeting identified four items for the ALERT-B (Assessment of Late Effects of RadioTherapy - Bowel) screening tool. ALERT-B was face tested for its usability and acceptability using cognitive interviews with 12 patients experiencing late gastrointestinal symptoms after pelvic radiotherapy. Thematic analysis and probe category were used to analyse interview transcripts. Interview data were presented to a group of experts to agree on the final content and format of the tool. ALERT-B was assessed for reliability and tested for validity against the Gastrointestinal Symptom Rating Scale in a clinical study (EAGLE). Results: Overall, the tool was found to be acceptable in terms of wording, response format and completion time. Participant-reported experiences, including lifestyle modifications and the psychological effect of the symptoms, led to further modifications of the tool. The refined tool includes three questions covering rectal bleeding, incontinence, nocturnal bowel movements and impact on quality of life, including mood, relationships and socialising. ALERT-B was successfully validated against the Gastrointestinal Symptom Rating Scale in the EAGLE study with the tool shown broadly to be internally consistent (Cronbach's α = 0.61 and all item-subscale correlation [Spearman] coefficients are > 0.6). Conclusion: The ALERT-B screening tool can be used in clinical practice to improve post-treatment supportive care by triggering the clinical assessment of patients suitable for referral to a gastroenterologist. Highlights: The ALERT-B screening tool was developed during an expert consensus meeting. Cognitive interviews showed the tool was easy to complete. Interview results helped to adapt the tool during a second consensus meeting. The tool has been successfully psychometrically validated.